HOXA5 Expression Is Elevated in Breast Cancer and Is Transcriptionally Regulated by Estradiol - Hussain, Imran; Deb, Paromita; Chini, Avisankar; Obaid, Monira; Bhan, Arunoday; Ansari, Khairul I.; Mishra, Bibhu P.; Bobzean, Samara A.; Udden, S. M. Nashir; Alluri, Prasanna G.; Das, Hriday K.; Brothers, Robert Matthew; et al. (Frontiers in Genetics, 2020)
HOXA5 is a homeobox-containing gene associated with the development of lung, gastro-intestinal tract, and vertebrae. Here, we have investigated potential roles and gene regulatory mechanism in HOXA5 in breast cancer cells. Our studies demonstrate that HOXA5 expression is elevated in breast cancer tissues, in estrogen receptor (ER)-positive breast cancer cells and is required for the viability of breast cancer cells. Biochemical studies show that HOXA5 gene expression is regulated by estradiol (E2) in cultured breast cancer cells in vitro. HOXA5 expression is also upregulated in vivo, in the mammary tissues of ovariectomized female rats. E2-induced HOXA5 expression is coordinated by estrogen receptors (ERs). Knockdown of either ERα or ERβ downregulated E2-induced HOXA5 expression. Additionally, ER-coregulators such as CBP/p300 (histone acetylases) and histone methylases (MLL2, MLL3), histone acetylation- and H3K4-trimethylation levels are enriched at the HOXA5 promoter in an E2-dependent manner. Overall, our studies demonstrate that HOXA5 is overexpressed in breast cancer and is transcriptionally regulated via estradiol in breast cancer cells.